Penatalaksanaan Tindakan Restrain Terhadap Penurunan Tingkat Kecemasan Pada Pasien Perilaku Kekerasan - Asdar Asdar; Basmalah Harun; Rusli Abdullah; Ekayanti A (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Introduction: Psychiatric patients often experience anxiety and agitation that has the potential to harm themselves and others, as for actions performed on new patients with anger or anxiety to prevent the risk of injury, one of which is fixation or restraint. Objective: Knowing how to decrease the level of anxiety of patients’ violent behaviours subjected to restraint actions. Method: Qualitative research with this case study approach using a descriptive method using Hamilton Anxiety Rating Scale measurements. Results: In this case study, there was an effect of restraint on the level of anxiety before and after being given restraint. Subject I, Before restraint, obtained a score of 35 for Severe anxiety and Subject II a score of 30 for severe anxiety. After a restraint procedure, the patient's anxiety level decreased until the second day in subject I, with a score of 24 moderate anxiety and II, with a score of 18 mild anxiety. Conclusion: There is a decrease in the anxiety level of patients subjected to restraint. Applying this restraint action can help patients control and recognise violent behaviour that can cause injury to themselves, others, and the environment